2001
DOI: 10.1177/030089160108700202
|View full text |Cite
|
Sign up to set email alerts
|

The Clinicopathologic Characteristics of Colorectal Cancer in Patients under 50 years of Age: Experience of an Oncology Center

Abstract: The presentation and outcome of the disease in young patients do not differ from those of older patients. A significant family history of colorectal cancer in the young patients showed the need for screening whereas the outcome of metastatic disease was poor. In order to anticipate long survival, early detection and aggressive treatment is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 16 publications
0
23
1
2
Order By: Relevance
“…Most studies found that in patients younger than age 40 years, the disease is diagnosed at a more advanced stage and with a higher proportion of mucinous histology and poor differentiation [5, 6, 8, 16–18]. However, other studies, usually of smaller size, did not confirm these data [7, 10, 11, 19]. In the present study, we found that CRC in young patients does indeed present at a higher stage, with a more extensive nodal involvement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies found that in patients younger than age 40 years, the disease is diagnosed at a more advanced stage and with a higher proportion of mucinous histology and poor differentiation [5, 6, 8, 16–18]. However, other studies, usually of smaller size, did not confirm these data [7, 10, 11, 19]. In the present study, we found that CRC in young patients does indeed present at a higher stage, with a more extensive nodal involvement.…”
Section: Discussionmentioning
confidence: 99%
“…O’Connell et al [5] reviewed more than 60 publications, some from more than four decades ago, and concluded that young patients (younger than age 40 years) have poorer outcome, unless the disease is diagnosed at a very early stage. In contrast, more recent studies showed that age by itself does not worsen prognosis when survival is adjusted for stage [7, 8, 11, 17–19]. Others reported that young age may even improve prognosis in certain stages [6, 10, 16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 When left untreated, the prognosis of metastatic cases is poor, with the median survival being 5-9 months. 6 Whereas the median survival time is 20-22 months and 5-year survival is 5% in unresectable metastatic colon cancers with systemic spread, survival rates of longer than 5 years have been demonstrated in approximately 50% of patients with resectable pulmonary metastases. 7 In lung metastases of colorectal cancers, complete resection is a potentially curative treatment if the primary tumor is under control, there is no evidence of extrathoracic involvement, all nodules can be removed with planned surgery, and the lung reserve is suitable for resection.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the development of metastasis is accepted as the main cause of death, the most common sites of distant metastasis are the liver and lung 5 . When left untreated, the prognosis of metastatic cases is poor, with the median survival being 5–9 months 6 . Whereas the median survival time is 20–22 months and 5‐year survival is 5% in unresectable metastatic colon cancers with systemic spread, survival rates of longer than 5 years have been demonstrated in approximately 50% of patients with resectable pulmonary metastases 7 .…”
Section: Introductionmentioning
confidence: 99%